Reverse water gas shift catalyst and its preparation method and application

Through specific formulations and preparation methods, a counterwater vapor transformation catalyst containing magnesium aluminum spinel phase was prepared, which solved the problem that existing catalysts could not simultaneously improve catalytic activity, high temperature stability and reduce costs, and achieved efficient counterwater vapor transformation reaction and low-cost industrial application.

CN116272955BActive Publication Date: 2025-05-09CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111508086.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-10
Publication Date
2025-05-09
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

The existing counter-water vapor transformation catalysts cannot take into account the problems of improving catalytic activity, high temperature stability and reducing costs.

Method used

Using specific formulations and preparation methods, a counter-water vapor transformation catalyst containing 2-8% by weight of Cr2O3, 5-16% by weight of TiO2, 20-30% by weight of MgO and 50-70% by weight of Al2O3 was prepared, which contained a magnesium-aluminum spinel phase, and the performance of the catalyst was improved by hydrothermal aging and reducing gas contact.

Benefits of technology

The reverse water vapor transformation reaction with high catalytic activity and good high temperature stability was achieved, effectively inhibiting the methanation reaction, the CH4 selectivity at 650°C was less than 0.2%, the activity retention rate was greater than 80%, and the preparation cost was reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272955B_ABST
    Figure CN116272955B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalysts used in the reverse water-gas shift reaction, and discloses a reverse water-gas shift catalyst and a preparation method thereof, as well as the application of the catalyst in the reverse water-gas shift reaction. Based on the total amount of the reverse water-gas shift catalyst, the reverse water-gas shift catalyst contains 2-8% by weight of Cr2O3, 5-16% by weight of TiO2, 20-30% by weight of MgO, and 50-70% by weight of Al2O3; wherein, the reverse water-gas shift catalyst contains a magnesium aluminate spinel phase. The reverse water-gas shift catalyst provided by the present invention can effectively inhibit the methanation reaction, the CH4 selectivity at 650 °C is less than 0.2%, and it has good high-temperature stability. After the accelerated deactivation experiment, the activity retention rate is greater than 80%. It can realize the efficient reverse water-gas shift reaction of H2 and CO2, approaching the thermodynamic equilibrium conversion rate. Compared with noble metal catalysts, the preparation cost is lower, which is more conducive to large-scale industrial applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts used in reverse water-gas shift reaction, and in particular to a reverse water-gas shift catalyst and a preparation method thereof, as well as application of the catalyst in reverse water-gas shift reaction. Background Art

[0002] Reverse water gas shift technology (RWGS) is the reverse reaction of the water gas shift (WGS) reaction. CO2 can be converted into valuable CO through the RWGS reaction, and then synthesized with H2 into oil or chemicals. It is a feasible way to utilize CO2 as a resource.

[0003] At present, the RWGS reaction catalysts that have been studied more can be divided into supported metal catalysts, composite oxide catalysts and transition metal carbide catalysts. Supported metal catalysts are divided into precious metal catalysts and non-precious metal catalysts. Precious metal catalysts have good catalytic activity in the RWGS reaction, but their use is limited due to their high prices. In recent years, the non-precious metal catalysts used in RWGS reaction research mainly include Cu, Ni, Mo, etc. The application of non-precious metal catalysts in RWGS reactions mainly has the disadvantages of poor high-temperature stability and easy sintering and deactivation. The catalyst surface can be modified by doping additives to achieve the effect of inhibiting the high-temperature deactivation of the catalyst. However, the current research on metal catalysts is mostly carried out at low temperatures below 500°C, and the methane selectivity is low. For a strongly endothermic reaction such as RWGS, conditions above 500°C are required for the conversion rate to be economical. For metal catalysts, at high temperatures (especially above 600°C), methanation side reactions are inevitable. According to thermodynamic analysis, once the methanation reaction occurs, the conversion rate of CO2 and CO selectivity will be significantly reduced. In addition, some studies believe that BaCe x Zr 0.8-x Y 0.16 Zn 0.04 O3、BaZr 0.8 Y 0.2 O3、BaZr 0.8 Y 0.16 Zn 0.04 Several types of perovskite catalysts have good high temperature stability in the reverse water gas shift reaction. Mo2C, as a hydrogenation catalyst, has similar chemical properties to precious metal catalysts. It has been reported that Mo2C catalysts are used in RWGS reactions and have better performance than CeO2-supported Pt-based catalysts under the same reaction conditions.

[0004] The industrial application of RWGS will take into account factors such as catalyst performance and cost. Although precious metal catalysts have high catalytic activity, their high prices will affect their industrial application. Composite oxide and carbide catalysts such as perovskite have advantages in high temperature stability and cost, but their performance needs to be further improved. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that the reverse water gas shift catalyst in the prior art cannot simultaneously improve the catalytic activity and high temperature stability and reduce the cost, and to provide a reverse water gas shift catalyst and a preparation method thereof, as well as the application of the catalyst in the reverse water gas shift reaction. The reverse water gas shift catalyst has high catalytic activity, good high temperature stability and low preparation cost.

[0006] In order to achieve the above object, the first aspect of the present invention provides a reverse water gas shift catalyst, which comprises 2-8 wt% Cr2O3, 5-16 wt% TiO2, 20-30 wt% MgO and 50-70 wt% Al2O3 based on the total amount of the reverse water gas shift catalyst;

[0007] Wherein, the reverse water gas shift catalyst contains a magnesium aluminum spinel phase.

[0008] A second aspect of the present invention provides a method for preparing a reverse water gas shift catalyst, the method comprising the following steps:

[0009] (1) kneading an alumina binder, a magnesium-containing compound, a titanium-containing compound, a chromium-containing compound and water to obtain a mixture;

[0010] (2) Extruding the mixture, and performing a first drying and a first calcination to obtain a catalyst precursor A;

[0011] (3) subjecting the catalyst precursor A to hydrothermal aging, and then subjecting it to a second drying and a second calcination to obtain a catalyst precursor B;

[0012] (4) contacting the catalyst precursor B with a reducing gas containing hydrogen to obtain a reverse water gas shift catalyst;

[0013] The magnesium-containing compound is magnesium hydroxide, which is in nano-flake form and has an average particle size of 100-500 nm; the alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, and the titanium-containing compound is calculated as TiO2. The feeding amounts of the alumina binder, the magnesium-containing compound and the titanium-containing compound satisfy that: the molar amount of MgO is greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO is 1-1.1:1.

[0014] The third aspect of the present invention provides the use of the reverse water gas shift catalyst as described in the first aspect or the reverse water gas shift catalyst prepared according to the method described in the second aspect in a reverse water gas shift reaction.

[0015] Through the above technical scheme, the method provided by the present invention adopts a specific formula, and by controlling the dosage relationship of each raw material, and coordinating hydrothermal aging, the obtained reverse water vapor shift catalyst contains 2-8 weight % of Cr2O3, 5-16 weight % of TiO2, 20-30 weight % of MgO and 50-70 weight % of Al2O3 based on the total amount of the reverse water vapor shift catalyst. The reverse water vapor shift catalyst contains a magnesium aluminum spinel phase and has no free magnesium oxide impurities. Among them, the active component Cr2O3 is highly dispersed on the carrier formed by Al / Mg / Ti oxide, and has a strong interaction with the carrier, which is higher than that of the ZrO2 carrier. The strong interaction improves the stability of nano Cr2O3 particles on the carrier surface, so that its grains are not easy to grow at high temperatures and cause catalyst deactivation. The reverse water vapor shift catalyst provided by the present invention can effectively inhibit methanation reaction, has a CH4 selectivity of less than 0.2% at 650°C, and has good high-temperature stability. After accelerated deactivation experiments, the activity retention rate is greater than 80%, and can achieve efficient reverse water vapor shift reaction of H2 and CO2, close to the thermodynamic equilibrium conversion rate. Compared with precious metal catalysts, the preparation cost is lower and it is more conducive to large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is the XRD spectrum of the reverse water gas shift catalyst prepared in Example 1;

[0017] Figure 2 This is the H2-TPR diagram of the reverse water gas shift catalyst prepared in Example 1. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] A first aspect of the present invention provides a reverse water gas shift catalyst, which comprises 2-8 wt% Cr2O3, 5-16 wt% TiO2, 20-30 wt% MgO and 50-70 wt% Al2O3, based on the total amount of the reverse water gas shift catalyst;

[0020] Wherein, the reverse water gas shift catalyst contains a magnesium aluminum spinel phase.

[0021] According to some embodiments of the present invention, the reverse water vapor shift catalyst contains a magnesium aluminum spinel phase. The magnesium aluminum spinel phase in the catalyst can not only serve as a carrier of the active component Cr2O3, but also can work together with other components in the catalyst to provide partial catalytic activity, so that the catalyst has high reverse water vapor shift activity and good high-temperature stability. Preferably, in the XRD spectrum of the reverse water vapor shift catalyst, diffraction peaks of MgAl2O4 appear at 2θ of 19°, 37°, 45°, 60° and 66°. More preferably, in the XRD spectrum of the reverse water vapor shift catalyst, no diffraction peak of MgO appears, which is beneficial to improving the reverse water vapor shift activity and high-temperature stability of the catalyst.

[0022] According to some embodiments of the present invention, preferably, the reverse water vapor shift catalyst also contains a magnesium titanate phase; more preferably, the magnesium titanate phase is a magnesium metatitanate phase; in the XRD spectrum of the reverse water vapor shift catalyst, diffraction peaks of magnesium metatitanate (MgTiO3) appear at 2θ of 21°, 24°, 33°, 35°, 49° and 53.5°. The above preferred embodiments can further improve the strength of the catalyst while ensuring that the catalyst has high reverse water vapor shift activity and high temperature stability.

[0023] According to some embodiments of the present invention, preferably, in the reverse water gas shift catalyst, the molar ratio of Al2O3 to TiO2 is 1-8: 1, preferably 1-5: 1. The reverse water gas shift catalyst has the above-mentioned specific molar relationship, which is conducive to further promoting the formation of MgAl2O4 and MgTiO3 phases in the catalyst.

[0024] According to some embodiments of the present invention, preferably, in the reverse water gas shift catalyst, the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30-100: 1, preferably 30-50: 1. The reverse water gas shift catalyst has the above-mentioned specific molar relationship, which is conducive to further promoting the high dispersion of Cr2O3 in the catalyst and avoiding sintering and deactivation of nano-Cr2O3 particles at high temperature.

[0025] According to some embodiments of the present invention, preferably, the specific surface area of ​​the reverse water gas shift catalyst is 180-300m 2 / g, preferably 200-250m 2 / g. The reverse water gas shift catalyst has a high specific surface area, which is conducive to promoting the high dispersion of the active component Cr2O3 on the Al / Mg / Ti oxide carrier, further improving the interaction between the active component Cr2O3 and the carrier, and improving the stability of nano Cr2O3 particles on the carrier surface, so as to further improve the catalytic activity and high temperature stability of the catalyst in the reverse water gas shift reaction.

[0026] A second aspect of the present invention provides a method for preparing a reverse water gas shift catalyst, the method comprising the following steps:

[0027] (1) kneading an alumina binder, a magnesium-containing compound, a titanium-containing compound, a chromium-containing compound and water to obtain a mixture;

[0028] (2) Extruding the mixture, and performing a first drying and a first calcination to obtain a catalyst precursor A;

[0029] (3) subjecting the catalyst precursor A to hydrothermal aging, and then subjecting it to a second drying and a second calcination to obtain a catalyst precursor B;

[0030] (4) contacting the catalyst precursor B with a reducing gas containing hydrogen to obtain a reverse water gas shift catalyst;

[0031] The magnesium-containing compound is magnesium hydroxide, which is in nano-flake form and has an average particle size of 100-500 nm; the alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, and the titanium-containing compound is calculated as TiO2. The feeding amounts of the alumina binder, the magnesium-containing compound and the titanium-containing compound satisfy that: the molar amount of MgO is greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO is 1-1.1:1.

[0032] According to some embodiments of the present invention, the method adopts a specific formula, and by controlling the dosage relationship of each raw material, and coordinating with hydrothermal aging, the obtained reverse water steam shift catalyst contains 2-8 weight% of Cr2O3, 5-16 weight% of TiO2, 20-30 weight% of MgO and 50-70 weight% of Al2O3 based on the total amount of the reverse water steam shift catalyst; wherein the reverse water steam shift catalyst contains a magnesium aluminum spinel phase.

[0033] According to some embodiments of the present invention, there is no particular restriction on the manner of introducing the components into the reverse water gas shift catalyst, and conventional introduction methods in the art may be adopted, such as kneading, impregnation, co-precipitation, etc., as long as the composition of the reverse water gas shift catalyst of the present invention can be obtained.

[0034] According to some embodiments of the present invention, the method uses a kneading method to introduce various components in the reverse water vapor shift catalyst. In step (1), the various raw materials constituting the reverse water vapor shift catalyst are mixed by kneading. Water is added during the kneading to form a dough-like billet with elasticity. Preferably, the amount of water used is 10-20% by weight of the total weight of the alumina binder, magnesium-containing compound, titanium-containing compound and chromium-containing compound. During the kneading process, the amount of raw materials of various components can be sufficient to obtain the composition of the reverse water vapor shift catalyst of the present invention.

[0035] According to some embodiments of the present invention, preferably, the alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3, and the feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound satisfy: the molar ratio of Al2O3 to TiO2 is 1-8:1, preferably 1-5:1.

[0036] According to some embodiments of the present invention, preferably, the alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3, and the feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound satisfy: the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30-100:1, preferably 30-50:1.

[0037] According to some embodiments of the present invention, preferably, in step (1), the feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound are such that the obtained reverse water gas shift catalyst contains a magnesium-aluminum spinel phase;

[0038] More preferably, the feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound are such that in the XRD spectrum of the obtained reverse water gas shift catalyst, diffraction peaks of MgAl2O4 appear at 2θ of 19°, 37°, 45°, 60° and 66°.

[0039] According to some embodiments of the present invention, preferably, in step (1), the feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound are such that the obtained reverse water gas shift catalyst also contains a magnesium titanate phase; more preferably, the magnesium titanate phase is a magnesium metatitanate phase; the feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound are such that in the XRD spectrum of the obtained reverse water gas shift catalyst, diffraction peaks of MgTiO3 appear at 2θ of 21°, 24°, 33°, 35°, 49° and 53.5°.

[0040] According to some embodiments of the present invention, preferably, in step (1), the alumina binder is selected from at least one of pseudo-boehmite, amorphous aluminum hydroxide and boehmite, preferably pseudo-boehmite.

[0041] According to some embodiments of the present invention, preferably, the titanium-containing compound is selected from at least one of metatitanic acid hydrate, metatitanic acid and nano titanium dioxide, preferably metatitanic acid hydrate.

[0042] According to some embodiments of the present invention, preferably, the chromium-containing compound is selected from at least one of chromium nitrate, chromium acetate and chromium oxalate, preferably chromium nitrate and / or chromium acetate.

[0043] According to some embodiments of the present invention, in step (2), the mixture is extruded, and subjected to a first drying and a first calcination to obtain a catalyst precursor A. This step is used to shape the mixture; the first drying and the first calcination steps can convert the components in the shaped product into oxide forms.

[0044] According to some embodiments of the present invention, preferably, the first drying conditions include: a temperature of 80-250° C., preferably 100-200° C.; and a time of 1-25 h, preferably 2-20 h.

[0045] According to some embodiments of the present invention, preferably, the conditions for the first calcination include: a temperature of 300-700° C., preferably 400-600° C.; and a time of 1-10 h, preferably 3-8 h.

[0046] According to some embodiments of the present invention, in step (3), the catalyst precursor A is subjected to hydrothermal aging, and then subjected to a second drying and a second calcination to obtain a catalyst precursor B. The hydrothermal aging step can optimize the catalyst precursor A to remove free MgO in the catalyst, and at the same time, cooperate with the specific formulation of the method, and control the relationship between the amounts of each raw material to achieve the formation of the magnesium aluminum spinel phase. The hydrothermal aging can be to place the catalyst precursor A in a closed container and immerse it in water, and heat the container so that the material therein is hydrothermally aged under autogenous pressure.

[0047] According to some embodiments of the present invention, preferably, the hydrothermal aging conditions include: a temperature of 100-200° C., preferably 100-150° C.; and a time of 4-12 h, preferably 6-10 h.

[0048] According to some embodiments of the present invention, in step (3), the second drying and second calcination steps are used to remove moisture from the material obtained after hydrothermal aging and convert various components in the material into oxide forms to obtain catalyst precursor B.

[0049] According to some embodiments of the present invention, preferably, the second drying conditions include: a temperature of 80-150° C., preferably 100-120° C.; and a time of 2-25 h, preferably 2-20 h.

[0050] According to some embodiments of the present invention, preferably, the conditions of the second calcination include: a temperature of 400-900° C., preferably 500-800° C.; and a time of 1-10 h, preferably 3-8 h.

[0051] According to some embodiments of the present invention, in step (4), the catalyst precursor B is contacted with a reducing gas containing hydrogen to obtain a reverse water gas shift catalyst. During the contacting process, CrO3 contained in the catalyst precursor B is reduced to Cr2O3.

[0052] According to some embodiments of the present invention, there is no particular limitation on the reducing gas containing hydrogen, as long as the preparation of the reverse water gas shift catalyst having the above-mentioned components can be achieved. The reducing gas can be a reducing gas conventionally used in the art for activating the reverse water gas shift catalyst, for example, it can be pure hydrogen or a reducing gas containing hydrogen (for example, a mixed gas of hydrogen and an inert gas, in which the content of hydrogen can be 10-90% by volume; the inert gas can be at least one of nitrogen, argon, neon and helium). The reducing gas can also be the feed gas in the reverse water gas shift reaction.

[0053] According to some embodiments of the present invention, preferably, the reverse water gas shift catalyst does not need to undergo additional activation and reduction operations before the reverse water gas shift reaction, and during the reverse water gas shift reaction, activation and reduction can be achieved under the action of the reducing gas H2 in the raw gas. However, the existing metal-based reverse water gas shift catalyst needs to undergo additional activation and reduction operations before use to reduce the metal oxide to metal, thereby achieving the designed activity. If it is reduced only by raw gas, it is impossible to achieve a high activity in the initial stage of the reaction, and a long activity improvement process is required, which wastes the raw gas.

[0054] According to some embodiments of the present invention, preferably, the H2 content in the raw gas is 50-70% by volume, preferably 55-65% by volume.

[0055] According to some embodiments of the present invention, preferably, the CO2 content in the raw gas is 15-30% by volume, preferably 20-25% by volume.

[0056] According to some embodiments of the present invention, preferably, the contact conditions include: pressure of 1-5 MPa, preferably 2-5 MPa; temperature of 500-800°C, preferably 600-700°C; volume space velocity of 5000-40000h -1 , preferably 10000-20000h -1 .

[0057] The third aspect of the present invention provides the use of the reverse water gas shift catalyst as described in the first aspect or the reverse water gas shift catalyst prepared according to the method described in the second aspect in a reverse water gas shift reaction.

[0058] According to some embodiments of the present invention, preferably, the conditions of the reverse water gas shift reaction include: a pressure of 1-5 MPa, preferably 2-5 MPa; a temperature of 500-800° C., preferably 600-700° C.; a volume space velocity of 5000-40000 h -1 , preferably 10000-20000h -1 .

[0059] The reverse water vapor shift catalyst provided by the present invention can effectively inhibit the methanation reaction in the reverse water gas shift reaction, and the CH4 selectivity at 650°C is less than 0.2%, and the high-temperature stability is good. After the accelerated deactivation experiment, the activity retention rate is greater than 80%, and the efficient reverse water vapor shift reaction of H2 and CO2 can be realized, which is close to the thermodynamic equilibrium conversion rate. Compared with precious metal catalysts, the preparation cost is lower and it is more conducive to large-scale application.

[0060] The present invention will be described in detail below through examples.

[0061] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained from commercial sources.

[0062] Among them, titanic acid hydrate was purchased from Shanghai Qiandu Industrial Co., Ltd.

[0063] The composition of the catalyst was determined by a ZSX Primus II X-ray fluorescence spectrometer (XRF) from Rigaku;

[0064] The XRD spectrum of the catalyst was measured by an X-ray diffractometer. The powder X-ray diffractometer was purchased from Bruker Company and its model was D8 advance.

[0065] The specific surface area of ​​the catalyst was measured by a nitrogen physical adsorption instrument, which was purchased from Micromeritics Company and has a model of tristarII 3020-M.

[0066] The catalyst strength was measured using a particle strength tester from VINCI.

[0067] The H2-TPR temperature-programmed reduction test was carried out on an AutoChem II 2920 chemical adsorption device from Micromeritics. The sample loading was 50 mg, and 99.999% helium was purged at 200°C for 1 hour to remove adsorbed trace water, and then the temperature was lowered to 80°C. 10 vol% H2 / Ar was used as the reducing gas, and TCD was used as the detector. The flow rate of the reducing gas was 50 mL / min, and the temperature was increased to 980°C at a heating rate of 10°C / min.

[0068] Example 1 - used to illustrate the reverse water gas shift catalyst provided by the present invention and its preparation method

[0069] Example 1

[0070] (1) 350 g of pseudo-boehmite (Al2O3 content of 70 wt%) and 165 g of magnesium hydroxide (flaky, average particle size of 200 nm, MgO content of 68 wt%) were mixed uniformly in the mixing hopper of an extruder.

[0071] (2) Weigh 100 g of titanate hydrate (TiO2 content: 50 wt%) and add it to the material obtained in step (1) and mix well.

[0072] (3) Dissolve 155 g of Cr(NO3)3·9H2O in 100 g of deionized water to prepare a solution, then add the obtained Cr(NO3)3 solution to the material obtained in step (2), and stir in the mixing hopper of the extruder for 1 hour to mix evenly to obtain a mixture. The feeding amounts of pseudo-boehmite, magnesium hydroxide and metatitanic acid hydrate satisfy that the molar amount of MgO is greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO is 1.09:1.

[0073] (4) The mixture obtained in step (3) is extruded on an extruder to obtain a molded sample with a diameter of 3 mm.

[0074] (5) The molded sample obtained in step (4) was dried at 120°C for 2 h, and then calcined at 500°C for 4 h to obtain catalyst precursor A.

[0075] (6) The catalyst precursor A obtained in step (5) is placed in a hydrothermal reactor and hydrothermally aged at 100° C. for 6 h. The hydrothermally aged product is then dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a catalyst precursor B.

[0076] (7) contacting the catalyst precursor B obtained in step (6) with a raw gas (wherein the content of CO2 is 23.7 vol%, the content of H2 is 62.4 vol%, the content of N2 is 1.3 vol%, and the content of CO is 12.6 vol%), and the contact conditions include: temperature of 650°C, pressure of 2 MPa, volume space velocity of 20000 h -1 , and obtain a reverse water gas shift catalyst.

[0077] The composition of the catalyst is: 6.7 weight percent Cr2O3, 11.5 weight percent TiO2, 25.7 weight percent MgO and 56.1 weight percent Al2O3; wherein the molar ratio of Al2O3 to TiO2 is 3.8:1; and the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30:1.

[0078] The XRD spectrum of the catalyst is shown in Figure 1 As shown, compared with the standard spectrum, it is determined that the catalyst has characteristic peaks of MgAl2O4 at 2θ of 19°, 37°, 45°, 60° and 66°, characteristic peaks of MgTiO3 at 2θ of 21°, 24°, 33°, 35°, 49° and 53.5°, and no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst. In addition, the XRD of the catalyst cannot detect the Cr2O3 crystal phase, indicating that Cr2O3 is highly dispersed in the catalyst.

[0079] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 238 m 2 / g.

[0080] The strength of the catalyst is shown in Table 1.

[0081] Example 2

[0082] A reverse water gas shift catalyst was prepared according to the method of Example 1, except that the amount of pseudo-boehmite was 290 g, the amount of magnesium hydroxide was 160 g, the amount of titanate hydrate was 120 g, and the amount of Cr(NO3)3·9H2O was 87 g. The amounts of pseudo-boehmite, magnesium hydroxide and titanate hydrate satisfied the following conditions: the molar amount of MgO was greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO was 1.02:1. The remaining raw materials, steps, conditions, etc. were the same as those in Example 1 to obtain a reverse water gas shift catalyst.

[0083] The composition of the catalyst is: 4.3 weight % Cr2O3, 15.4 weight % TiO2, 28.0 weight % MgO and 52.3 weight % Al2O3; wherein the molar ratio of Al2O3 to TiO2 is 2.6:1; and the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 50:1.

[0084] XRD test shows that the XRD spectrum of the catalyst has characteristic peaks of MgAl2O4 and MgTiO3, but no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst. In addition, the XRD of the catalyst cannot detect the Cr2O3 crystal phase, indicating that Cr2O3 is highly dispersed in the catalyst.

[0085] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 213 m 2 / g.

[0086] The strength of the catalyst is shown in Table 1.

[0087] Example 3

[0088] A reverse water gas shift catalyst was prepared according to the method of Example 1, except that the amount of pseudo-boehmite was 370 g, the amount of magnesium hydroxide was 170 g, the amount of titanate hydrate was 85 g, and the amount of Cr(NO3)3·9H2O was 118 g. The amounts of pseudo-boehmite, magnesium hydroxide and titanate hydrate satisfied the following conditions: the molar amount of MgO was greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO was 1.07:1. The remaining raw materials, steps, conditions, etc. were the same as those in Example 1 to obtain a reverse water gas shift catalyst.

[0089] The composition of the catalyst is: 5.1 weight % Cr2O3, 9.7 weight % TiO2, 26.3 weight % MgO and 58.9 weight % Al2O3; wherein the molar ratio of Al2O3 to TiO2 is 4.8:1; and the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 40:1.

[0090] XRD test shows that the XRD spectrum of the catalyst has characteristic peaks of MgAl2O4 and MgTiO3, but no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst. In addition, the XRD of the catalyst cannot detect the Cr2O3 crystal phase, indicating that Cr2O3 is highly dispersed in the catalyst.

[0091] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 247 m 2 / g.

[0092] The strength of the catalyst is shown in Table 1.

[0093] Example 4

[0094] A reverse water gas shift catalyst was prepared according to the method of Example 1, except that the amount of pseudo-boehmite was 370 g, the amount of magnesium hydroxide was 170 g, the amount of titanate hydrate was 55 g, and the amount of Cr(NO3)3·9H2O was 116 g. The amounts of pseudo-boehmite, magnesium hydroxide and titanate hydrate satisfied the following conditions: the molar amount of MgO was greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO was 1.01:1. The remaining raw materials, steps, conditions, etc. were the same as those in Example 1 to obtain a reverse water gas shift catalyst.

[0095] The composition of the catalyst is: 5.2 weight percent Cr2O3, 6.5 weight percent TiO2, 27.2 weight percent MgO and 61.1 weight percent Al2O3; wherein the molar ratio of Al2O3 to TiO2 is 7.4:1; and the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 40:1.

[0096] XRD test shows that the XRD spectrum of the catalyst has characteristic peaks of MgAl2O4 and MgTiO3, but no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst. In addition, the XRD of the catalyst cannot detect the Cr2O3 crystal phase, indicating that Cr2O3 is highly dispersed in the catalyst.

[0097] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 229 m 2 / g.

[0098] The strength of the catalyst is shown in Table 1.

[0099] Example 5

[0100] A reverse water gas shift catalyst was prepared according to the method of Example 1, except that the amount of pseudo-boehmite was 350 g, the amount of magnesium hydroxide was 165 g, the amount of titanate hydrate was 100 g, and the amount of Cr(NO3)3·9H2O was 50 g. The amounts of pseudo-boehmite, magnesium hydroxide and titanate hydrate satisfied the following conditions: the molar amount of MgO was greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO was 1.09:1. The remaining raw materials, steps, conditions, etc. were the same as those in Example 1 to obtain a reverse water gas shift catalyst.

[0101] The composition of the catalyst is: 2.3 weight percent Cr2O3, 12.0 weight percent TiO2, 26.9 weight percent MgO and 58.8 weight percent Al2O3; wherein the molar ratio of Al2O3 to TiO2 is 3.8:1; and the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 93:1.

[0102] XRD test shows that the XRD spectrum of the catalyst has characteristic peaks of MgAl2O4 and MgTiO3, but no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst. In addition, the XRD of the catalyst cannot detect the Cr2O3 crystal phase, indicating that Cr2O3 is highly dispersed in the catalyst.

[0103] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 231 m 2 / g.

[0104] The strength of the catalyst is shown in Table 1.

[0105] Comparative Example 1

[0106] (1) Add 381 g of ZrO2 powder (average particle size of 5 nm, content of 100 wt%) into the mixing hopper of the extruder, then weigh 50 g of zirconium gel (ZrO2 content of 20 wt%) and add it to the ZrO2 powder and mix well.

[0107] (2) 90 g of Cr(NO3)3·9H2O was dissolved in 100 g of deionized water to prepare a solution, and then the obtained Cr(NO3)3 solution was added to the material obtained in step (1), and stirred in the mixing hopper of the extruder for 1 h to mix evenly, thereby obtaining a mixture.

[0108] (3) The mixture obtained in step (2) is extruded on an extruder to obtain a molded sample with a diameter of 3 mm.

[0109] (4) The molded sample obtained in step (3) was dried at 120°C for 2 h, and then calcined at 500°C for 4 h to obtain catalyst precursor A.

[0110] (5) The catalyst precursor A obtained in step (4) is placed in a hydrothermal reactor and hydrothermally aged at 100° C. for 6 h. The product after hydrothermal aging is then dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a catalyst precursor B.

[0111] (6) contacting the catalyst precursor B obtained in step (5) with a raw gas (wherein the content of CO2 is 23.7 vol%, the content of H2 is 62.4 vol%, the content of N2 is 1.3 vol%, and the content of CO is 12.6 vol%), and the contact conditions include: temperature of 650°C, pressure of 2 MPa, volume space velocity of 20000 h -1 , and obtain Cr2O3 / ZrO2 catalyst.

[0112] The composition of the catalyst is: 4.2 wt % Cr2O3 and 95.8 wt % ZrO2.

[0113] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 81 m 2 / g.

[0114] The strength of the catalyst is shown in Table 1.

[0115] Comparative Example 2

[0116] (1) 406 g of pseudo-boehmite (Al2O3 content of 70 wt%) and 157 g of magnesium hydroxide (flaky, average particle size of 200 nm, MgO content of 68 wt%) were mixed uniformly in the mixing hopper of an extruder.

[0117] (2) 66.5 g of Ni(NO3)2·6H2O was dissolved in 100 g of deionized water to prepare a solution, and then the obtained Ni(NO3)2 solution was added to the material obtained in step (1), and stirred in the mixing hopper of the extruder for 1 h to mix evenly, thereby obtaining a mixture.

[0118] (3) The mixture obtained in step (2) is extruded on an extruder to obtain a molded sample with a diameter of 3 mm.

[0119] (4) The molded sample obtained in step (3) was dried at 120°C for 2 h, and then calcined at 500°C for 4 h to obtain catalyst precursor A.

[0120] (5) The catalyst precursor A obtained in step (4) is placed in a hydrothermal reactor and hydrothermally aged at 100° C. for 6 h. The product after hydrothermal aging is then dried at 120° C. for 2 h and then calcined at 800° C. for 4 h to obtain a catalyst precursor B.

[0121] (6) The catalyst precursor B obtained in step (5) is contacted with a mixed gas (wherein H2 is 20 vol%, N2 is 80 vol%), and the contact conditions include: temperature of 650°C, pressure of 2 MPa, volume space velocity of 20000 h -1 , and obtain Ni / MgAl2O4 catalyst.

[0122] The composition of the catalyst is: 3.3 wt% Ni, 26.4 wt% MgO and 70.3 wt% Al2O3.

[0123] XRD testing shows that the XRD spectrum of the catalyst has a characteristic peak of MgAl2O4, but no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst.

[0124] According to nitrogen adsorption analysis, the specific surface area of ​​the catalyst is 242m 2 / g.

[0125] The strength of the catalyst is shown in Table 1.

[0126] Comparative Example 3

[0127] A reverse water gas shift catalyst was prepared according to the method of Example 1, except that the amount of pseudo-boehmite was 360 g, the amount of magnesium hydroxide was 140 g, the amount of titanate hydrate was 376 g, and the amount of Cr(NO3)3·9H2O was 190 g. The amounts of pseudo-boehmite, magnesium hydroxide and titanate hydrate satisfied the following conditions: the molar amount of MgO was less than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO was 2.04:1. The remaining raw materials, steps, conditions, etc. were the same as those in Example 1 to obtain a reverse water gas shift catalyst.

[0128] The composition of the catalyst is: 6.3 weight percent Cr2O3, 32.9 weight percent TiO2, 16.7 weight percent MgO and 44.1 weight percent Al2O3; wherein the molar ratio of Al2O3 to TiO2 is 1.05:1; and the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30:1.

[0129] XRD test shows that the XRD spectrum of the catalyst has characteristic peaks of MgAl2O4 and MgTiO3, but no diffraction peak of MgO, indicating that there is no MgO phase impurity in the catalyst. In addition, the XRD of the catalyst cannot detect the Cr2O3 crystal phase, indicating that Cr2O3 is highly dispersed in the catalyst.

[0130] Nitrogen adsorption analysis showed that the specific surface area of ​​the catalyst was 228 m 2 / g.

[0131] The strength of the catalyst is shown in Table 1.

[0132] Test Case

[0133] The catalysts prepared in Examples 1-5 and Comparative Examples 1-3 were evaluated and subjected to H2-TPR programmed temperature reduction test and accelerated deactivation experiment, respectively. The results are shown in Table 1.

[0134] 1. Catalyst evaluation

[0135] The test was carried out on a micro-reaction evaluation device with a catalyst loading of 0.5 g. The catalyst was contacted with the raw gas for catalyst evaluation under the following contact conditions: temperature 650°C, pressure 2 MPa, volume space velocity 20,000 h -1 The raw gas composition (v / v) is CO2 / H2 / N2 / CO=23.7% / 62.4% / 1.3% / 12.6%.

[0136] 2. H2-TPR programmed temperature reduction test

[0137] The H2-TPR temperature-programmed reduction test was carried out on an AutoChem II 2920 chemical adsorption device from Micromeritics. The sample loading was 50 mg, and 99.999% helium was purged at 200°C for 1 hour to remove adsorbed trace water, and then the temperature was lowered to 80°C. 10 vol% H2 / Ar was used as the reducing gas, and TCD was used as the detector. The flow rate of the reducing gas was 50 mL / min, and the temperature was increased to 980°C at a heating rate of 10°C / min.

[0138] The present invention illustratively provides the H2-TPR diagram of the reverse water gas shift catalyst prepared in Example 1, as shown in Figure 2 As shown in the figure, it can be seen that 321℃ is the reduction peak of CrO3 to Cr2O3.

[0139] 3. Catalyst accelerated deactivation experiment

[0140] In the accelerated deactivation experiment, the catalyst was first heated at 650°C, 2 MPa and a volume space velocity of 20,000 h -1 The catalyst was then contacted with the feed gas (same composition as above) for evaluation, the temperature was raised to 800°C and operated for 8 hours, then dropped to 650°C, and the activity retention rates of the catalysts were compared.

[0141] Table 1

[0142]

[0143]

[0144] It can be seen from the above results that the reverse water gas shift catalyst provided by the present invention is applied to the reverse water gas shift reaction, has a high CO2 conversion rate, can effectively inhibit the methanation reaction, has a CH4 selectivity of less than 0.2% at 650°C, and has good high temperature stability. After the accelerated deactivation experiment, the activity retention rate is greater than 80%.

[0145] Comparing the CO2 conversion rates of the catalysts of Example 1 and Comparative Example 1, it can be seen that the catalyst activity of Example 1 is significantly higher than that of Comparative Example 1, and is equivalent to the thermodynamic equilibrium conversion rate of CO2 under this condition (the calculated value is 51.5%). The main reason is that the specific surface area of ​​the catalyst of Example 1 is much higher than that of Comparative Example 1. Under the condition of loading the same weight of active components, the active components are highly dispersed, and the active sites are fully exposed, so that the catalyst activity of Example 1 is high. At the same time, the activity retention rate of the catalyst of Example 1 is 91%, while the activity retention rate of Comparative Example 1 is only 65%. It can be seen that the stability of the catalyst of Example 1 is higher than that of Comparative Example 1, and the reason can be explained from the H2 programmed temperature reduction experiment. The reduction temperature of the catalyst of Example 1 is 321°C, while the reduction temperature of Comparative Example 1 is 297°C, which proves that the interaction between the active components and the carrier in the catalyst of Example 1 is much higher than that of Comparative Example 1, so that the active component particles are not easy to aggregate and grow at high temperatures, resulting in a decrease in activity, showing a higher thermal stability. In addition, the catalyst of Example 1, whose carrier contains MgAl2O4 structure, has significantly higher anti-hydration stability than the catalyst of Comparative Example 2, whose carrier is ZrO2.

[0146] By comparing Example 1 with Comparative Example 2, it can be seen that the CO2 conversion rate of Comparative Example 2 is lower, while the CH4 selectivity is higher, and the methanation side reaction is obvious. The reason is that the active component of Comparative Example 2 is metal Ni, and the methanation activity of the metal is very significant at high temperature, thereby reducing the activity of the catalyst in the reverse water gas shift reaction and improving the CH4 selectivity.

[0147] By comparing Example 1 with Comparative Example 3, it can be seen that the activity retention rate of the accelerated deactivation experiment of Comparative Example 3 is low. The reason is that the molar amount of MgO added in the preparation process of Comparative Example 3 is less than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO is 2.04:1, which leads to a significant decrease in the content of MgAl2O4 in the catalyst, thereby reducing the catalyst's anti-hydration stability at high temperatures.

[0148] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A reverse water gas shift catalyst, characterized in that: Based on the total amount of the reverse water steam shift catalyst, the elements in the reverse water steam shift catalyst are calculated as Cr2O3, TiO2, MgO, and Al2O3, respectively, and the reverse water steam shift catalyst contains 2-8 weight % of Cr2O3, 5-16 weight % of TiO2, 20-30 weight % of MgO, and 50-70 weight % of Al2O3; wherein the reverse water gas shift catalyst contains a magnesium aluminum spinel phase and has no free magnesium oxide impurities; The reverse water gas shift catalyst also contains a magnesium titanate phase, and Cr2O3 is highly dispersed on a carrier formed by Al / Mg / Ti oxide.

2. The reverse water gas shift catalyst according to claim 1, wherein In the XRD spectrum of the reverse water gas shift catalyst, diffraction peaks of MgAl2O4 appear at 2θ of 19°, 37°, 45°, 60° and 66°.

3. The reverse water gas shift catalyst according to claim 1 or 2, wherein: In the XRD spectrum of the reverse water gas shift catalyst, diffraction peaks of MgTiO3 appear at 2θ of 21°, 24°, 33°, 35°, 49° and 53.5°.

4. The reverse water gas shift catalyst according to claim 1 or 2, wherein: In the reverse water gas shift catalyst, the molar ratio of Al2O3 to TiO2 is 1-8:1, and / or In the reverse water gas shift catalyst, the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30-100:1; and / or The specific surface area of ​​the reverse water gas shift catalyst is 180-300 m 2 / g.

5. The reverse water gas shift catalyst according to claim 4, wherein: In the reverse water gas shift catalyst, the molar ratio of Al2O3 to TiO2 is 1-5:1, calculated as oxides.

6. The reverse water gas shift catalyst according to claim 4, wherein In the reverse water gas shift catalyst, the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3, calculated as oxides, is 30-50:

1.

7. The reverse water gas shift catalyst according to claim 4, wherein: The specific surface area of ​​the reverse water gas shift catalyst is 200-250 m 2 / g.

8. A method for preparing a reverse water gas shift catalyst according to any one of claims 1 to 7, comprising the following steps: (1) kneading an alumina binder, a magnesium-containing compound, a titanium-containing compound, a chromium-containing compound and water to obtain a mixture; (2) Extruding the mixture into strips, and performing a first drying and a first calcination to obtain a catalyst precursor A; (3) subjecting the catalyst precursor A to hydrothermal aging, and then subjecting it to a second drying and a second calcination to obtain a catalyst precursor B; (4) contacting the catalyst precursor B with a reducing gas containing hydrogen to obtain a reverse water gas shift catalyst; in, The magnesium-containing compound is magnesium hydroxide, which is in nano-flake form and has an average particle size of 100-500nm; the alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, and the titanium-containing compound is calculated as TiO2. The feeding amounts of the alumina binder, the magnesium-containing compound and the titanium-containing compound satisfy that: the molar amount of MgO is greater than the molar amount of Al2O3, and the ratio of the sum of the molar amounts of Al2O3 and TiO2 to the molar amount of MgO is 1-1.1:

1.

9. The method according to claim 8, wherein: The alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3. The feed amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound satisfy that the molar ratio of Al2O3 to TiO2 is 1-8:1; and / or The alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3. The feed amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound satisfy the following requirement: the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30-100:1; and / or The alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3. The feeding amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound are such that the elements in the prepared reverse water steam shift catalyst are calculated as Cr2O3, TiO2, MgO and Al2O3, respectively. The reverse water steam shift catalyst contains 2-8 weight % of Cr2O3, 5-16 weight % of TiO2, 20-30 weight % of MgO and 50-70 weight % of Al2O3.

10. The method according to claim 9, wherein: The alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3. The feed amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound satisfy that the molar ratio of Al2O3 to TiO2 is 1-5:

1.

11. The method according to claim 9, wherein: The alumina binder is calculated as Al2O3, the magnesium-containing compound is calculated as MgO, the titanium-containing compound is calculated as TiO2, and the chromium-containing compound is calculated as Cr2O3. The feed amounts of the alumina binder, the magnesium-containing compound, the titanium-containing compound and the chromium-containing compound satisfy that the ratio of the sum of the molar amounts of Al2O3, TiO2 and MgO to the molar amount of Cr2O3 is 30-50:

1.

12. The method according to claim 8 or 9, wherein: In step (1), the alumina binder is selected from at least one of pseudo-boehmite, amorphous aluminum hydroxide and boehmite; and / or The titanium-containing compound is selected from at least one of metatitanic acid hydrate, metatitanic acid and nano titanium dioxide; and / or The chromium-containing compound is selected from at least one of chromium nitrate, chromium acetate and chromium oxalate.

13. The method according to claim 12, wherein: In step (1), the alumina binder is pseudo-boehmite.

14. The method according to claim 12, wherein: The titanium-containing compound is metatitanic acid hydrate.

15. The method according to claim 12, wherein: The chromium-containing compound is chromium nitrate and / or chromium acetate.

16. The method according to claim 8 or 9, wherein: In step (2), the first drying conditions include: temperature of 80-250°C; time of 1-25h; and / or The first calcination conditions include: temperature of 300-700° C.; time of 1-10 h; and / or In step (3), the hydrothermal aging conditions include: temperature of 100-200°C; time of 4-12h; and / or The second drying conditions include: temperature of 80-150°C; time of 2-25h; and / or The second calcination conditions include: temperature of 400-900° C.; time of 1-10 h; and / or In step (4), the reducing gas containing hydrogen is the raw material gas; The H2 content in the raw gas is 50-70% by volume; and / or, the CO2 content in the raw gas is 15-30% by volume; And / or, the contact conditions include: pressure of 1-5 MPa; temperature of 500-800°C; volume space velocity of 5000-40000h -1 .

17. The method according to claim 16, wherein: In step (2), the first drying conditions include: temperature of 100-200° C.; time of 2-20 h.

18. The method according to claim 16, wherein: The first calcination conditions include: temperature of 400-600° C.; time of 3-8 hours.

19. The method according to claim 16, wherein: In step (3), the hydrothermal aging conditions include: temperature of 100-150° C. and time of 6-10 h.

20. The method according to claim 16, wherein: The second drying conditions include: temperature of 100-120° C.; time of 2-20 h.

21. The method according to claim 16, wherein: The second calcination conditions include: temperature of 500-800° C.; time of 3-8 hours.

22. The method according to claim 16, wherein: The H2 content in the raw gas is 55-65% by volume.

23. The method according to claim 16, wherein: The content of CO2 in the raw gas is 20-25% by volume.

24. The method according to claim 16, wherein: The contact conditions include: pressure of 2-5 MPa; temperature of 600-700°C; volume space velocity of 10000-20000h -1 .

25. Use of the reverse water gas shift catalyst according to any one of claims 1 to 7 in a reverse water gas shift reaction.

Citation Information

Patent Citations

  • Method for preparing sulfur-tolerant shift catalyst

    CN108654631A

  • Sulfur tolerant shift catalyst and preparation method thereof

    CN108786837A